Tribological characteristics of few-layer graphene over Ni grain and interface boundaries. Issue 12 (7th March 2016) - Tripathi, Manoj; Awaja, Firas; Paolicelli, Guido; Bartali, Ruben; Iacob, Erica; Valeri, Sergio; Ryu, Seunghwa; Signetti, Stefano; Speranza, Giorgio; Pugno, Nicola Maria
Abstract : The tribological properties of metal-supported few-layered graphene depend strongly on the grain topology of the metal substrate. Abstract : The tribological properties of metal-supported few-layered graphene depend strongly on the grain topology of the metal substrate. Inhomogeneous distribution of graphene layers at such regions led to variable landscapes with distinguishable roughness. This discrepancy in morphology significantly affects the frictional and wetting characteristics of the FLG system. We discretely measured friction characteristics of FLG covering grains and interfacial grain boundaries of polycrystalline Ni metal substrate via an atomic force microscopy (AFM) probe. The friction coefficient of FLG covered at interfacial grain boundaries is found to be lower than that on grains in vacuum (at 10 −5 Torr pressure) and similar results were obtained in air condition. Sliding history with AFM cantilever, static and dynamic pull-in and pull-off adhesion forces were addressed in the course of friction measurements to explain the role of the out-of-plane deformation of graphene layer(s). Finite element simulations showed good agreement with experiments and led to a rationalization of the observations. Thus, with interfacial grain boundaries the FLG tribology can be effectively tuned.